The Golden Age Of Russian Literature - Kurbanova M.O; Turgunova Gulchira; Zufarova Khurshida; Mamadalieva Noila (Zien Journals, 2022)
The article highlights the Golden Age of Russian literature, illuminated by the genius of A.S. Pushkin, N.V. Gogol, I.S. Turgenev, F.M. Dostoevsky, L.N. Tolstoy A.P. Chekhov, with the brilliance of the talent of a whole constellation of major writers, Russian literature has rapidly come a long way, has moved into the ranks of the greatest literatures of the world. The development of realism in Russian literature differed significantly during this period from its development on Western European soil. At this time, Russian literature in its significance came to the forefront of the world literary process.
Keywords: Golden age; brilliance; talent; constellation